Produção, isolamento e identificação de metabólito com atividade citotóxica de cultura de Streptomyces carpaticus - Ferreira, Douglas (2011)
This study addresses the production, isolation and identification of the substance present in culture broth of Streptomyces carpaticus which showed high biological activity against human tumor cell lines HL-60 (promyelocytic leukemia), MDA-MB 435 (breast carcinoma ), HCT-8 (colon carcinoma), SF-295 (glioblastoma). Cultures of Streptomyces carpaticus in culture medium DSMZ 65 were performed in shake flasks. Initial bioassays of the culture broth extracts showed antiproliferative activity close to 100% inhibition against the tumor cell lines. In order to obtain greater volume of culture medium to isolate the compound of interest, bioreactor cultivations were performed in bioreactor with 12 L working volume. After microfiltration and ultrafiltration of the culture broth through a 0.22- micron and 3 kDa membrane filter, the retentate was then subjected to partitioning using different organic solvents (ethyl acetate and n-buthanol). The fractionation of the extracts was bioguided based on the bioassay results and on HPLC-DAD-MS analysis. The fractionations led to the isolation and identification of the cyclodepsipeptide Valinomycin as responsible for cytotoxic activity. In addition, the results showed the strain as isopalmitic acid producer. Values of inhibition concentration (IC50) obtained for the compound isolated from the broth, against various tumor cell lines, presented low values ranging between 2 and 10 ng.mL-1. The use of bench scale bioreactor, bioguided fractionation and mass spectrometry proved to be fundamental to the development of this study, because it was evidenced that the discovered compound responsible for the antiproliferative activity is produced at very low concentrations. The use of HPLC-DADMS/ MS by selective ion monitoring was able to propose a methodology to estimate Valinomycin production in four different culture media tested, an important result for future studies regarding the development of the production and purification process of Valinomycin by S. carpaticus.